(3GdJHjGf aj EYQGH GdbQBfs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi habfG dMaX cJGHg hhbafG Ydi GdLdjd ef Mceg hGMcGeg hBOGjg hCdgefG eYGfjg hhLhg EYQGHg s
(3BNQgG (B:s
(3gPG BNQ eG JjSQ ef EedGA cJGH GdJHjGf ai EYQGH GdbQBf hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO GdfHi hYdi Bdg hCUMGHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI ebGHdIs
(3hbjO GdNJGe eKHJ HBNQgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B208s
Keywords: (3GdfMhs